Should QANTAS be privatised, and if so, how? - Neish, Richard (Graduate paper (University College of Central Queensland. School of Business), 1990)
"This report analyses the future possibility of the Privatisation of QANTAS AIRWAYS LIMITED, Australia's International Airline which at present is wholly owned by the Commonwealth of Australia. There has been a great deal written and discussed in the media, in Parliament and in the Private Sector in general, especially in the last five years, about the long term benefits to Australia by the Privatisation of QANTAS and the possible less attractive results of privatisation. This report will analyse many of these statements and put them in perspective to the real issues involved."--P. iii.